The Use of Technology in the Islamic Boarding School Curriculum: A Phenomenological Study - Arbain Nurdin; Hairul Fauzi; Nurul Zainab; Maria Ulfa; Khadeejah Alrawashdeh (Edudeena : Journal of Islamic Religious Education, 2026)
This study explores the lived experiences and perceptions of santri related the use of technology in Islamic Boarding School curriculum, such as in literacy programs. In the context of the rapid development of information and communication technology (ICT), pesantren as traditional educational institutions face the phenomenon of adaptation and integration of technology in various aspects, including literacy development. This research uses a qualitative approach with the type of transcendental phenomenology, and involves santri at Padepokan Kyai Mudrikah Kembang Kuning Pamekasan who have implemented technology in their curriculum. Data collection was conducted through semi-structured in-depth interviews and participatory observation, as well as documentation. The collected data were then analyzed using the phenomenological analysis method, which focuses on identifying essential themes related to the experiences and perceptions of santri related the use of technology in Islamic Boarding School curriculum espesially in literacy programs, then developing textural (what santri experience) and structural (how santri experience) descriptions, and describing the essence of santri experiences the use of technology in literacy programs and their perceptions related to the meaning of literacy. The results show that the experience of using technology in Islamic Boarding School curriculum in literacy programs is very diverse and personal. The themes that emerged included feelings of motivation and enthusiasm for wider access to learning resources, the challenges of adapting to new digital platforms, and reflections on the meaning of literacy itself in the digital era.